Addressing Surgical Instrument Oversupply: A Focused Literature Review and Case-Study in Orthopedic Hand Surgery. (November 2022) - Helmkamp, Joshua K.; Le, Elliot; Hill, Ian; Hein, Rachel; Mithani, Suhail; Codd, Patrick; Richard, Marc
Background: Instrument oversupply drives cost in the operating room (OR). We review previously reported methodologies for surgical instrument reduction and report a pilot methodology for optimizing instrument supply via ethnographic instrument tracking of thumb carpometacarpal (CMC) arthroplasties. Additionally, we report a cost analysis of instrument oversupply and potential savings of tray optimization methods. Methods: Instrument utilization was tracked over 8 CMC arthroplasties conducted by 2 surgeons at an ambulatory surgery center of a large academic hospital. An optimized supply methodology was designed. A cost analysis was conducted using health-system-specific data and previously published research. Results: After tracking instrument use in 8 CMC arthroplasties, a cumulative total of 59 out of the 120 instruments in the Hand & Foot (H&F) tray were used in at least 1 case. Two instruments were used in all cases, and another 20 instruments were used in at least 50% of the cases. Using a reduced tray with 59 instruments, potential cost savings for tray reduction in 60 cases were estimated to be $2086 without peel-packing and $2356 with peel-packing. The estimated cost savings were lower than those reported in literature due to a reduced scope and exclusion of OR time cost in the analysis. Conclusions: Instrument oversupply drives cost at our institution's ambulatory surgery center. Ethnography is a cost-effective method to track instrument utilization and determine optimal tray composition for small services but is not scalable to large health systems. The time and cost required to observe sufficient surgeries to enable supply reduction to motivate the need for more efficient methods to determine instrument utility.